Zad 1,Uprość wyrażenia
a) 5 razy(xy)=
b) 3a/4 razy (-2a/3)=
c) -2x razy(-3xy)=
d) x-x/2-x/3=
e) -4razy (-x/2)razy(-2x/4)=
f) x+1/2+2x-1/4=
g) -(x+1)+(2x+4)=
h) 3(a kwadrat-4)-(-a kwadrat+2)=

zad2.zapisz w postaci jak najprostrzej sumy algebraicznej.
a) (x+3)(x-7)=
b) -3(2x-1)(z+6)=
c) -(y-1)(2y+4)=
d) 2a kwadrat-(a+6)(2a-1)=
e) 3(x kwadrat-1)-(x-3)(x+2)=

1

Odpowiedzi

2010-04-11T13:21:19+02:00
Zad 1,Uprość wyrażenia
a) 5 razy(xy)= 5xy
b) 3a/4 razy (-2a/3)=-a kwadrat/2
c) -2x razy(-3xy)=6xkwadrat y
d) x-x/2-x/3=11x/6
e) -4razy (-x/2)razy(-2x/4)=-xkwadrat
f) x+1/2+2x-1/4=3x+1/4
g) -(x+1)+(2x+4)=x+3
h) 3(a kwadrat-4)-(-a kwadrat+2)=4a kwadrat -14

zad2.zapisz w postaci jak najprostrzej sumy algebraicznej.
a) (x+3)(x-7)=xkwadrat -7x +3x -21=-4x-21
b) -3(2x-1)(z+6)=(-6x+3)(z+6)=-6xz-36x+3z+18
c) -(y-1)(2y+4)=-(2ykwadrat +4y -2y -4)=-2ykwadrat-2y-4
d) 2a kwadrat-(a+6)(2a-1)=11a-6
e) 3(x kwadrat-1)-(x-3)(x+2)=2xkawdrat -x-9